The timing of last hemodialysis influences the prognostic value of serum lactate levels in predicting mortality of end-stage renal disease patients with sepsis in the emergency department. Issue 7 (19th February 2021) - Chu, Chun Chieh; Su, Chih Min; Chen, Fu Cheng; Cheng, Chi Yung; Cheng, Hsien Hung; Te Kung, Chia
Abstract : Abstract: Sepsis is a life-threatening condition, and serum lactate levels have been used to predict patient prognosis. Studies on serum lactate levels in patients undergoing regular hemodialysis who have sepsis are limited. This study aimed to determine the predictive value of serum lactate levels for sepsis-related mortality among patients who underwent last hemodialysis at three different times before admission to the emergency department (ED). This retrospective cohort study was conducted from January 2007 to December 2013 in southern Taiwan. All hemodialysis patients with sepsis, receiving antibiotics within 24 hours of sepsis confirmation, admitted for at least 3 days, and whose serum lactate levels were known were examined to determine the difference in the serum lactate levels of patients who underwent last hemodialysis within 4 hours (Groups A), in 4–12 hours (Group B), and beyond 12 hours (Group C) before visited to the ED. All the continuous variables, categorical variables and mortality were compared by using Kruskal-Wallis test or Mann-Whitney test, the χ 2 or Fisher exact tests, and multiple logistic regression model, respectively. A total of 490 patients were enrolled in the study, and 8.0% (39), 21.5% (84), and 74.9% (367) of the patients were in Group A, Group B and Group C, respectively; the serum lactate levels (2.91 vs 2.13 vs 2.79 mmol/L, respectively; P  = .175) and 28-day in-hospital mortality (17.9% vs 14.6% vs 22.9%) showed no statistically significant difference between 3 groups. The association between serum lactate levels and 28-day in-hospital mortality was reliable in Group B ( P  = .002) and Group C ( P  < .001), but it was unreliable in Group A ( P  = .629). Serum lactate level has acceptable sensitivity in predicting 28-day in-hospital mortality among patients with sepsis who undergo last hemodialysis after 4 hours, but is not reliable when the last hemodialysis takes place within 4 hours.